The Positive Association Between Empathy and Self-Esteem in Chinese Medical Students: A Multi-Institutional Study - Huang, Lei; Thai, Jessica; Zhong, Yuan; Peng, Hao; Koran, Jessica; Zhao, Xu-Dong (Frontiers in Psychology, 2019)
Background: Empathy is an important element of the physician-patient relationship for medical students. However, most studies have shown that it declines during undergraduate medical education. Less explored in the literature is how empathy interrelates with the psychological elements of medical students, in particular self-esteem. This study examined the relationship between empathy and self-esteem to explore other possible ways to improve medical students’ empathy. Methods: A stratified sampling strategy was used to select 1690 medical students from 3 medical institutions in Shanghai to participate in this study. The questionnaires used to collect data included the Jefferson Scale of Physician Empathy-Student Version (JSPE-S), the Rosenberg Self-esteem Scale (RSES), and a self-made inventory on personal information. Descriptive analysis, independent t-test, One-Way ANOVA, and linear regression were used to analyze the data. Results: The mean empathy score among medical students was 102.73±12.64. “age,” “perception of the importance of empathy,” “academic pressure,” “desire to be a doctor after graduation,” and “self-esteem” were significant predictors of empathy (P< 0.05) and the adjusted R2 was 0.462. The correlation matrix between empathy and self-esteem was significant (r=0.510, P < 0.01). Self-esteem explained 15.5% of the variation of empathy in the final regression model. Conclusions: There was a positive association between self-esteem and empathy. Self-esteem should be considered as one of the many potential determinant factors which contribute to medical students’ empathy in addition to age, academic pressure, attitude towards empathy and future career, which all also play a critical role in medical student empathy. Enhancing medical students’ self-esteem may be an efficacious way to improve medical students’ empathy.